Тепловое излучение взрыва: оценки риска термического поражения людей и возникновения пожаров. II - Stepanov, Константин; Stanchits, Л.; Stankevich, Ю. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
In this paper we continue the study of thermal radiation from explosion, initiated in [1]. Obtained there data on the radiative characteristics of the fireball explosion and plume diffusion combustion of hydrocarbon fuel are used for determining the doses of radiation and heat fluxes on the target. For this purpose, we use the theory of angular coefficients that allows evaluate the irradiance parameters for arbitrary oriented targets located on the earth's surface. Calculation of thermal loads on the target in the vicinity of the energy release zone is performed. The impact of radiation from the explosion and fire compared with the criteria of the thermal damage of people and ignition of combustible materials.